Healing a Wary, Self-cultivating Society through Education - Hisam Kim (Korea Development Institute (KDI), 2018)
Can education improve Korea's self-cultivating society which has left its people untrusting of others? Reforming public education, particularly eliminating rote-based learning and encouraging horizontal and participatory classes, will enhance peer relationships, trust and cooperation to ultimately contribute to reversing the decline in social capital. - The significance of social capital, which is formed of interpersonal relationships and interaction, is recognized throughout society. - Amid the growing popularity of the "each to his own" mentality, Korea is experiencing a continuous decline in mutual trust. - The low degree of happiness in Koreans is due to the lack of social capital. - In Northern European countries that apply horizontal collaborative methods, people with higher education show stronger social trust. But, this is not the case for Korea and East European countries wherein one-sided lectures are more dominant. - How children are taught is more signifiant to the cultivation of social capital than what is taught. What is critical to fostering social capital is how to teach, not what to teach. - A high proportion (81%) of Korean respondents described high school as a 'battlefield.' - Korean undergraduates have low public trust and prefer self-help methods to collective solutions. - Korea has the lowest percentage of those who believe that the general public and government officials will meet social norms. - Korea shows low willingness to make donations and has weak solidarity. - About 73% of Korean respondents preferred a secluded residential environment for privacy protection over communication and interaction. - Korean undergraduates believe that as the level of education increases, the level of cooperative sprit decreases. - Social capital increased further among students who were more frequently exposed to PBL activities. - Students who received a horizontal-type education showed more increases in their network of friends and better perceptions about social capital at the end of the semester. - Peer relationships fostered in the course of horizontal interactions were found to improve perceptions and attitudes about social capital. - Having experienced random grouping in class, students became more receptive to cooperating with others who are unfamiliar. - Horizontal interaction could be enhanced by adopting constructivism through, for example, PBL and flipped classroom programs. - It is necessary to extend evaluation systems to an appropriate degree, such as team-based, absolute, student participatory and processfocused formats. - An innovative education environment such as bottomup changes in classes should be developed and HR systems for faculty need to be redesigned to go hand in hand with educational innovation. - Transforming teaching methods to be more horizontal and participatory is an important agenda that will contribute to not only enhancing social capital but also to fostering those with skills needed in the future.
Keywords: 330